Determinants of financial well-being among public employees in Putrajaya, Malaysia - Mokhtar, Nuradibah; Abdul Rahim @ Abdul Wahab, Husniyah (Universiti Putra Malaysia Press, 2017)
People generally see finance as anything that can be associated with the economic situation of the family. Thus, managing finances among individuals may result in satisfaction or dissatisfaction towards their financial situation, which is called financial well-being. Previous research regarding financial well-being has largely focused on factors such as financial stress, financial knowledge and financial behaviour. However, influences by the locus of control and work environment on financial well-being were little explored. Thus, this research studied the factors affecting financial well-being among public employees in Putrajaya, Malaysia. This study is a quantitative study using a set of online structured questionnaire to obtain the necessary data. A total of 207 completed questionnaires, out of 316 responded questionnaires, were analysed using Statistical Package for Social Science (SPSS) version 21. The results indicated that financial stress, work environment, locus of control and financial behaviour were significantly associated with financial well-being. In addition, financial stress was the strongest factor affecting financial well-being followed by work environment. At the end, the outcome of this study can be used for a better understanding of employees' financial behaviour, which can be enhanced through financial education at the workplace.